(untitled) (Colombia Medica, 2024)
Background: YouTube is one of the most used social media platforms for accessing health information. Objective: To evaluate the quality and reliability of YouTube videos about chronic prostatitis. Methods: YouTube search using the keywords "kronik prostatit" for Turkish videos and ’chronic prostatitis’ for English videos were done. The videos were evaluated through modified-Quality Criteria for Consumer Health Information (DISCERN), the Journal of the American Medical Association (JAMA), the Global Quality Scale (GQS), and Video Power Index (VPI) scoring systems. The characters of the videos were also recorded and analyzed. Results: Of the 65 Turkish videos, videos of health professions (HPv) were uploaded 58 and seven videos of laypersons (Lv). There were no significant differences between the views, like counts, VPI, or the content quality and reliability of HPv and Lv. Of the 62 English videos, videos of HP were uploaded 40 and 22 videos of laypersons. Although HPv were found to have greater DISCERN and JAMA values, Lv had more views, view ratio, and Video Power Index than HPv. When all 127 videos were evaluated regardless of the language, Lv were found to have more total views and ratings, but there were no significant differences between like ratio, VPI, DISCERN, JAMA, and GQS values between the two groups. Conclusions: Most YouTube videos about chronic prostatitis did not have enough quality and reliable information. Health associations should be more attentive to posting more content videos of sufficient quality and reliability on social media platforms.